Postpartum-specific Vital Sign Reference Ranges. Issue 4 (22nd December 2021) - Green, L.J.; Pullon, R.; Mackillop, L.H.; Gerry, S.; Birks, J.; Salvi, D.; Davidson, S.; Loerup, L.; Tarassenko, L.; Mossop, J.; Edwards, C.; Gauntlett, R.; et al.
Abstract : ( Obstet Gynecol . 2021;137:295–304. doi: 10.1097/AOG.0000000000004239. PMID: 33417320) The majority of maternal deaths occur in the postpartum period (57% in the United States), compared with the antenatal and intrapartum periods. However, maternal deaths in the postpartum period have not been studied as extensively as the antenatal and intrapartum periods. Venous thromboembolism, hemorrhage, sepsis, and gestational hypertensive disorders are the leading causes of death during postpartum. Little data exists describing normal postpartum vital signs. This study aimed to estimate maternal postpartum vital sign ranges.